AI-driven precision agriculture in Eurasia-coordinated innovation for belt and road agricultural transformationin - Mitrokhin, M.; Soytong, K.; Song, J. J.; Mitrokhin, E. (My University, 2025)
International collaboration in AI based technologies in agriculture is essential factor to increase output and agriculture productivity. AI horizons/ alliance program aimed to increase awareness and accessibility of new agro markets and optimize supply routes in Eurasia. Precision agriculture is commonly used term that enables AI based instruments into practical agriculture works. Precision agriculture in Eurasia is undergoing a transformative wave powered by artificial intelligence (AI) and cross-border innovation. This article examines how AI-driven technologies including agro-drones for aerial crop monitoring, satellite-based NDVI analysis, image recognition for pest and disease detection, advanced weather forecasting models, and decision support systems – are being deployed across Great Eurasia and Belt and Road Initiative (BRI) countries to boost agricultural productivity and sustainability. A particular focus is given to the Eurasian context countries like China, Kazakhstan, Uzbekistan, Russia and Thailand are leveraging AI to overcome climate and labor challenges, increase yields, and optimize resource use. The AI Horizons Alliance, a Sber-driven consortium, is highlighted as a coordinating body facilitating the exchange of AI technologies and expertise across borders. Real-world case studies demonstrate tangible benefits, such as up to 20% increases in crop yields, and 30% improvements in efficiency, and significant cost savings, achieved through AI-enabled precision farming. The article discusses the collaborative efforts under BRI frameworks, the integration of traditional knowledge with cutting-edge digital tools, and the role of international organizations in guiding this tech-driven agricultural transformation. Challenges from data sharing to capacity building are considered alongside prospects for broader adoption. The findings underscore that AI-driven precision agriculture, underpinned by coordinated Eurasian partnerships, holds to promise for enhancing food security and sustainable development across the region. It is a part of innovation organic agriculture.
Keywords: Agro-drones; Artificial intelligence; Image recognition; Precision agriculture; Smart farming